Rethinking Blended High Yielding Seed Varieties and Partial-Organic Fertilizer Climate Smart Agriculture Practices for Productivity and Farm Income Gains in the Drylands of Zimbabwe - Musara, Joseph P.; Bahta, Yonas T.; Musemwa, Lovemore; Manzvera, Joseph (Frontiers in Sustainable Food Systems, 2022)
Most blended climate smart agriculture (CSA) technologies focusing on seed-fertilizer combinations have either been marginally adopted or dis-adopted by smallholder farmers due to the nature of design and implementation. A data science research approach was used with 380 households in the mid-Zambezi Valley of Zimbabwe. The study examines impact of adopting a farmer initiated CSA practice combining improved sorghum seed variety and partial-organic fertilizer on household income and productivity among smallholder farmers in the drylands of Zimbabwe. A cross sectional household survey using multi stage sampling with purposive and stratified proportionate approaches was conducted. A structured questionnaire was utilized for data collection. Endogenous Switching Regression (ESR) model was utilized to account for self-selection bias of sampled farmers. Overall, a combination of farm specific factors (arable land, variable costs) and external factors (distance to the market, value of aid) have a bearing on the adoption decision and the associated impact on productivity and income. The counterfactual analysis shows that farmers who adopt the technology are relatively better off in productivity and income. Our findings highlight the significance of improving access to CSA practices which are initiated by the farmers using a bottom-up approach since they suit their operating contexts better. Tailor-made supporting programs including farmer networking platforms and decentralized markets need to be designed and scaled up by policymakers to encourage farmers to adopt blended soil fertility CSA practices in their farming practices. Networking arrangements need to be strengthened through local, government and private sector partnerships along the sorghum value chain.